Breathing peculiarities during the performance of the technical routine of the artistic swimming national teams of Russia and Egypt at the XXXII summer Olympic Games - Elsherif, O. A. E. M. A.; Solomatin, V. R. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the characteristic features of breathing in the national teams of Russia and Egypt in artistic swimming at the Olympic Games 2020 (2021).